The effects of minimum wage on males’ and females’ employment, earnings and hours of work in South Africa - Morapeli, Maipato (My University, 2022)
In this study we use the Difference-in-Differences estimator to investigate whether the effects of the national minimum wage on wages, hours of work, and employment differ for male and female workers in South Africa. We use panel data constructed from StatsSA’s Quarterly Labour Force Surveys from 2018Q2 to 2019Q3. Findings from our study show that on average, the national minimum wage has a positive effect on wages for females and males, but the effect was greater for males compared to females. This suggests a gender gap in the effect of the national minimum wage among South African workers. On the hours of work variable, our results provide proof that the effect of the national minimum wage on hours of work also differs for males and females. The estimates show that the national minimum has a negative wage effect on hours of work for females, while for males the law has a positive effect. On employment for female workers, the introduction of the national minimum wage negatively affected the chances of staying employed while for male workers, introducing the national minimum wage had no effect on the probability of staying employed. These results suggest that the national minimum wage contributes to gender inequalities in the South African labour market which requires complementary measures that aim toward closing the induced gender gaps.
A Research Report submitted in partial fulfilment of the Degree of Master of Commerce (Economic Science) in the School of Economics and Finance, University of the Witwatersrand, 2022